Islamic Economic Analysis Reviews: the Transparency of Top-up Banking - Rahma Yudi Astuti; Dhika Amalia Kurniawan (Universitas Darussalam Gontor, 2019)
Writing this paper is based on customers who are trapped with the facilities provided by the bank, called “top up”. Customers do not need to pay off the remaining loans, customers will receive a new schedule and a new loan ceiling. This is based on many problems experienced by bank customers. The extent to which transparency is applied by banks in accordance with PBI. No. 7/6/2005 is the aim of this study. This research is qualitative research with an evaluative-normative approach. From these problems, the bank in delivering it to customers about Top Up information has not conveyed transparently what should be conveyed to customers. Transparency to customers is very important in accordance with an Islamic economy based on sharia values and principles that can be applied in all aspects of business life and transactions of the Ummah Compliance with regulations issued by the government, namely PBI no. 7/6 / PBI / 2005 which is not yet fully operational in banking in general. With transparency being applied in Islamic economics, customers will know what their rights and obligations are. Transparency to customers is very important to prevent misunderstandings that can cause harm to customers..